Mapping Urban Spaces Designing the European City - Amistadi, Lamberto; Balducci, Valter; Bradecki, Tomasz; Prandi, Enrico; Schröder, Uwe (Taylor & Francis, 2021)
"Mapping Urban Spaces focuses on medium-sized European cities and more specifically on their open spaces from psychological, sociological, and aesthetic points of view. The chapters illustrate how the characteristics that make life in medium-sized European cities pleasant and sustainable - accessibility, ease of travel, urban sustainability, social inclusiveness - can be traced back to the nature of that space. The chapters develop from a phenomenological study of space to contributions on places and landscapes in the city. Centralities and their meaning are studied, as well as the social space and its complexity. The contributions focus on history and theory as well as concrete research and mapping approaches and the resulting design applications. The case studies come from countries around Europe including Poland, Italy, Greece, Germany, and France, among others. The book will be of interest to students, scholars, and practitioners in architecture, urban planning, and landscape architecture."